Pengaruh Mata Kuliah Kewirausahaan dan Lingkungan Keluarga Terhadap Minat Berwirausaha Mahasiswa Politeknik Purbaya - Sri Lestari (Lembaga Pengembangan Kinerja Dosen, 2025)
Purbaya Polytechnic has attempted to foster an entrepreneurial spirit in its students through the incorporation of entrepreneurship courses into the Informatics Engineering curriculum. The purpose of this study is to find out how entrepreneurship courses and family environment affect the desire of Informatics Engineering students on campus to become entrepreneurs. This study uses a quantitative approach to collect data through questionnaires. The respondents were students of batches 2023 (Semester 4) and 2022 (Semester 6). They have completed the entrepreneurship course. The purposive sampling method was used to draw a sample of students who were eligible for the entrepreneurship course: those who actively attended the course and had followed it from orientation to business development. To analyze the data, the SPSS program was used. Validity and reliability tests (Cronbach Alpha) were used to ensure the accuracy of the instruments. In addition, classical assumption tests such as heteroscedasticity and normality (through a one-sample Kolmogorov-Smirnov test with a significance threshold of more than 0.05) were used. The research hypotheses were tested with simple linear regression with a significance level of 0.05. The results of this study are expected to show how entrepreneurship education and family support affect students' entrepreneurial interest partially and simultaneously.